ONRECHTMATIGE OVERHEIDSDAAD: UNLAWFUL ACTS BY THE STATE IN INDONESIAN CONSTITUTIONAL LAW - Rizki Cintia Devi; Moh. Fadli; Bambang Hery Mulyono (CV. RADJA PUBLIKA, 2025)
Considering that the government's actions in carrying out its functions by using public and private legal instruments will ultimately intersect with the interests of citizens, a means of legal protection is needed to maintain a balance so that the objectives of the public interest can be achieved without necessarily sacrificing the rights of citizens protected by law. This research is a normative-research that studies legal objectives, values of justice, validity of legal rules, legal concepts, and legal norms. Normative legal research can also be said to be a process for finding legal rules, legal principles, and legal doctrines in order to answer the legal issues at hand. The source materials used in this research are primary legal materials, secondary legal materials and tertiary legal materials. Primary legal material is Indonesian Law. Furthermore, the data collected is analyzed qualitatively. The element of “against the law” in the formulation of administrative disputes referred to in Law Number 30 of 2014 concerning Government Administration is to interfere with the rights of others; second, contrary to the legal obligations of the perpetrator; third, contrary to decency; fourth, contrary to the decency, thoroughness, and careful attitude that a person should have in association with fellow citizens or against other people's objects. If these elements are fulfilled, the party aggrieved by the decision of the State Administrative Officer may file a lawsuit with the State Administrative Court. With the development of the concept of KTUN in Article 87 of Law No. 30/2014, it can be seen that concrete actions are one form of KTUN. Thus, the lawsuit against the existence of real actions which is an onrechtmatige overheidsdaad lawsuit which was previously the absolute competence of the District Court, has changed to the absolute competence of the State Administrative Court.